2010
DOI: 10.1021/ac100062t
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer Plate Heights for Capillaries Packed with Silica Colloidal Crystals

Abstract: Extremely uniform packing of colloidal silica in capillaries is shown. Reversed-phase electrochromatograms of DiI-C12 exhibit plate heights as low as 0.13 µm and a reduced plate height as low as 0.4, using 75 µm i.d. capillaries packed with 330 nm silica particles. The contribution from the A term is 0±20 nm in electrochromatography. The particles are shown to form colloidal crystals inside the capillaries. Optical images show Bragg diffraction, indicative of crystallinity; SEM images show face-centered cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 18 publications
7
74
1
Order By: Relevance
“…While there has not been a study of the role of order in dc field separation in a colloidal crystal, a study of long DNA separation under a pulsed electric field in a 3D colloidal array found that an ordered matrix improved the separation resolution over a disordered matrix [43]. We anticipate that dc electric field separations in 3D colloidal arrays will also benefit from increased array order, similar to the results for protein chromatography in colloidal crystals [44].…”
Section: Discussionsupporting
confidence: 59%
“…While there has not been a study of the role of order in dc field separation in a colloidal crystal, a study of long DNA separation under a pulsed electric field in a 3D colloidal array found that an ordered matrix improved the separation resolution over a disordered matrix [43]. We anticipate that dc electric field separations in 3D colloidal arrays will also benefit from increased array order, similar to the results for protein chromatography in colloidal crystals [44].…”
Section: Discussionsupporting
confidence: 59%
“…A typical SEM image is shown in Fig. 1B, confirming that the packing of silica particles is disordered, in contrast to our earlier work that shows (111) or (100) crystalline packing [19]. …”
Section: Resultssupporting
confidence: 78%
“…A very highly ordered silica colloidal crystal of 0.4×0.4 mm 2 has been made and was shown to separate DNA fragments by biased reptation 23. Packed inside capillaries, silica colloidal crystals have been demonstrated to give plate heights as low as 100 nm in the electrochromatography of a fluorescent dye, when corrected for injected width 24. The corrected plate height was contributed entirely by diffusion, within experimental error.…”
Section: Introductionmentioning
confidence: 82%